تأثير المعاملة بالمخصب الحيوي EM1 في نمو وإنتاجية البطاطا - بوراس, متيادي; زيدان, رياض; عيسى, ريم (Latakia University Journal -Biological Sciences Series, 2019)
The study was carried out at private farm in Banias during the spring of 2018. The experiment included four treatments(control without treating of EM1,spraying of EM1,spraying+soaking in EM1,soaking in EM1) with three replicates per treatment and fifteen plants each.The aim of this study was to test the effeciency of bifertilizer(EM1) in growth and yeild of potato SolanumTuberosumL. local variaty" Spunta".The design was based on completed randomized(no blocking) design and the results were statistically analyzed by using the genstat-12 statistical analysis program. The results showed that the soaking of potato tubers before planting in EM1 gave an increase of the tuber germination,and the number of stem .The use of bio-fertilizer EM1 led to improved plant growth by increasing the leaf area and height of the plant and significant differences from the control . The treatment of soaking + spraying increased the leaf area as it reached 9935 cm2 with (7709,7025.5600) cm2, and in yeild reached 6512 kg / don, compared to 5103.4395.33427 kg/don. نفذ البحث في الموسم الربيعي لعام 2018في ضواحي مدينة بانياس, تضمنت التجربة أربع معاملات (شاهد بدون رش, رش بالمخصب الحيوي EM1, نقع الدرنات بالمخصب EM1 +رش بالمخصبEM1 ,و نقع بالمخصب الحيويEM1) بأربع مكررات لكل معاملة وخمسة عشر نبات في كل مكرر.هدف البحث إلى دراسة تأثير المخصب الحيوي EM1 في نمو وإنتاجية نباتات البطاطا صنف Spunta , اعتمد في تنفيذ البحث التصميم العشوائي الكامل وتم تحليل النتائج إحصائياً باستخدام برنامج التحليل الإحصائيGenstat-12 . أظهرت النتائج أن نقع الدرنات بالمخصب الحيوي EM1قبل الزراعة ساهم في الإسراع من إنبات الدرنات, وزيادة عدد السوق المتشكلة , كما بينت النتائج أن استخدام المخصب الحيوي EM1 أدى إلى تحسين نمو النباتات من خلال زيادة مساحة المسطح الورقي ومتوسط ارتفاع النبات وبفروق معنوية عن الشاهد , تفوقت معاملة النقع بالمخصب EM1 +رش بالمخصب EM1(T3) بفروق معنوية في متوسط مساحة المسطح الورقي إذ بلغت 9935 سم2مقابل (7709,7025,5600)سم2,وفي الإنتاجية إذ بلغت 6512 كغ/دونم, مقابل (5103,4395,3427) كغ/دونم للمعاملات (الرش, النقع, والشاهد)بالترتيب.